1999
DOI: 10.1063/1.371317
|View full text |Cite
|
Sign up to set email alerts
|

Field emitters based on porous aluminum oxide templates

Abstract: The field-emission properties of cold cathodes produced using nano-porous anodic aluminum oxide (AAO) templates are reported. Several types of field emitters were fabricated: aligned copper nanowires grown halfway up the parallel nano-pores of the AAO; aligned multiwalled carbon nanotubes grown to the top of the pores; surfaces overgrown with random tangles of carbon nanotubes; and empty AAO templates. Significant field-emission currents (field enhancement values ∼ 1800) were obtained at threshold voltages as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(81 citation statements)
references
References 11 publications
3
76
1
Order By: Relevance
“…Reported values for g range from a few tens to ten thousand or more (Xu, 1995;Davydov et al, 1999). The knowledge of g enables the field F t at the surface of the emitting tip to be found from the macroscopic field, hence b from Eq.…”
Section: Introductionmentioning
confidence: 99%
“…Reported values for g range from a few tens to ten thousand or more (Xu, 1995;Davydov et al, 1999). The knowledge of g enables the field F t at the surface of the emitting tip to be found from the macroscopic field, hence b from Eq.…”
Section: Introductionmentioning
confidence: 99%
“…Ratio of anode to cathode currents is constant while the calculated enhancement factor was almost the same as the aspect ratio of the Co wires. The turn-on voltage (12 V/μm) is comparable to that of CNTs (1-10 V/μm) [Davydov et al, 1999]. Deviation from the F-N relationship (solid line) at higher fields is attributed to an undesired serial resistance (R = 4 MΩ) in the experimental set-up.…”
Section: Field-emission Electron Emittersmentioning
confidence: 89%
“…These excellent field emission properties of Ni-P catalyzed-CNTs may be attributed to the random orientation and small diameter of CNTs. As Davydov and co-workers 24 pointed out, perfectly aligned carbon nanotubes were less efficient field emitters and had lower field enhancement than chaotic carbon nanotubes. Groning and co-workers 25 also suggested that some random CNTs exhibited better field emission properties than aligned CNTs.…”
Section: Methodsmentioning
confidence: 99%